THE EFFECTS OF OUT-OF-PLANE SEISMIC ENERGY ON REFLECTIONS IN CRUSTAL-SCALE 2D SEISMIC SECTIONS - Drummond B.J.; Goleby B.R.; Hobbs R.W. (My University, 2004)
Crustal-scale seismic surveys mostly collect data along single profiles, and the data processing has an underlying assumption that the data have imaged two-dimension (2D) structure striking at right angles to the seismic profile. However, even small amounts of out-of-plane topography on a reflector can result in reflections that do not map the reflector shape accurately. Out-of-plane energy will migrate within the plane of the section to an apparent depth (represented as two-way-time, TWT) that is greater than the depth of the reflection point out of the plane of the section. It will fall within the plane of the section at depths less than, equal to or greater than the intersection of the reflector with the plane of the section, depending on both the amount of out-of-plane topographic relief on the reflector, and the offset of the topographic relief from the plane of the section. Reflectors that are a single surface can therefore be manifested in the seismic section as a band of several reflections, rather than a single reflection. More complex reflectors, such as shear zones that have a finite thickness because they are made up of several to many anastomosing layers of altered and anisotropic rock embedded in protolith, will appear as laterally short reflections within a laterally continuous reflection band. Other examples of such reflectors would be the Moho in some places, and rock with compositional layering. With increasing out-of-plane topographic relief on the reflector, the top of the reflection band for both single- and multi-layer reflectors will be a poor indicator of the top of the reflector in the Earth. The bottom of the reflection band will always be a poor indicator of the bottom of the reflector. Because out-of-plane energy can arrive at TWTs that are different from those of the reflector in the plane of the section, out-of-plane energy has the potential to interfere constructively or destructively with the in-plane energy. In synthetic data calculated for a simple model assuming one layer and topographic relief of 250 m over wavelengths of 4-5 km, similar to that imaged in a real sub-horizontal detachment, amplitudes ranged up to 2.6 times the expected amplitude for the layer. A model with anastomosing layers built to resemble a thick shear zone rather than a discrete fault surface allowed tuning between layers. The effects of out-of-plane energy when combined with the effects of tuning caused amplitudes up to 3.1 times those expected. Larger amplitudes could be achieved if a suitable model was contrived. The results indicate that care must be taken when calculating impedance contrasts using real data. The highest amplitude reflections are likely to yield overestimates of the true impedance contrast.
Keywords: Seismic; Out-of-plane energy; Amplitudes; Imaging